2009
DOI: 10.1007/s11274-009-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the yeast-extract signaling pathway leading to silymarin biosynthesis in milk thistle hairy root culture

Abstract: The biosynthesis of silymarin, a potent antihepatotoxic compound, from the dried fruits of Silybum marianum L. Gaertn in hairy root cultures can be stimulated by a yeast extract elicitor. These results correlated with culture time, and the biosynthesis reached a maximum of 0.47 mg g -1 DW by 72 h after culture (2-fold higher than the control). Lipoxygenase activity and linoleic acid content were stimulated by this treatment, suggesting that the jasmonate pathway may mediate the elicitor-induced accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Otherwise, SA plays important roles in regulating photosynthesis and accumulation of phenolic acid production [8]. In this respect, in vitro production of silymarin from S. marianum was investigated using different strategies; growth regulators and carbon sources [9], [10], [11], [12], [13], elicitors [14], [15], [16], [17] root and hairy root cultures [18], [19], [20], [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, SA plays important roles in regulating photosynthesis and accumulation of phenolic acid production [8]. In this respect, in vitro production of silymarin from S. marianum was investigated using different strategies; growth regulators and carbon sources [9], [10], [11], [12], [13], elicitors [14], [15], [16], [17] root and hairy root cultures [18], [19], [20], [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the elicitation effects might be due to other components, still not being identified (Ertola & Hours 1998). In many species it has been proven to stimulate or decrease different secondary metabolites, such as syringin, valeportriates, podophyllotoxin and silymarin (Kittipongpatana et al 2002;Shams-Ardakani et al 2005;Xu et al 2007;Hasanloo et al 2009). Our current work revealed that YE is a stimulating factor for TA production in A. acutangulus plant, which gradually boosted the contents of hyoscyamine and scopolamine in the root and stem in the range of 96 h treatment, the same as the key genes of TA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of experiments have demonstrated that MJ was able to stimulate the production of several compounds in many species (Ignatov et al 1996;Rijhwani & Shaks 1998;Dong & Zhong 2002;Wang & Zhong 2002;Vasconsuelo & Boland 2007). Yeast extract (YE), a kind of polysaccharide, was also been reported to have the ability to regulate increase or decrease different secondary metabolites in many species, such as syringin, valeportriates, podophyllotoxin and silymarin (Kittipongpatana et al 2002;Shams-Ardakani et al 2005;Xu et al 2007;Hasanloo et al 2009). Abscisic acid (ABA), also called resistant inducer element, is a key element which can balance the plant endogenous hormones and is relevant to growth-active substances.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of intermediate, precursors and catalytic enzymes involved in jasmonic acid biosynthetic pathways were reportedly observed following yeast extract elicitation (Yaguchi T et al, 2017;Hasanloo T et al, 2009). Thus, chitosan and yeast extract would bi-laterally enhance the aloe-emodin production through the jasmonic acid-signalling pathway and create a new synergistic elicitor duo.…”
Section: Simultaneous Double Elicitation On Aloe-emodin Productionmentioning
confidence: 94%